New light on a dark subject: comment - Miller, Matthew P.; Simone, Bailey E.; McKnight, Diane M.; Cory, Rose M.; Williams, Mark W.; Boyer, Elizabeth W. (Aquatic sciences, 2010)
In their article, “New light on a dark subject: On the use of fluorescence data to deduce redox states of natural organic matter,” Macalady and Walton-Day ( 2009 ) subjected natural organic matter (NOM) samples to oxidation, reduction, and photochemical transformation. Fluorescence spectra were obtained on samples, which were diluted “to bring maximum uvvisible absorbance values below 1.0.” The spectra were fit to the Cory and McKnight ( 2005 ) parallel factor analysis (PARAFAC) model, and consistent variation in the redox state of quinone-like moieties was not detected. Based on these results they concluded that fitting fluorescence spectra to the Cory and McKnight ( 2005 ) PARAFAC model to obtain information about the redox state of quinone-like moieties in NOM is problematic. Recognizing that collection and correction of fluorescence spectra requires consideration of many factors, we investigated the potential for inner-filter effects to obscure the ability of fluorescence spectroscopy to quantify the redox state of quinone-like moieties. We collected fluorescence spectra on Pony Lake and Suwannee River fulvic acid standards that were diluted to cover a range of absorbance wavelengths, and fit these spectra to the Cory and McKnight ( 2005 ) PARAFAC model. Our results suggest that, in order for the commonly used inner-filter correction to effectively remove inner-filter effects, samples should be diluted such that the absorbance at 254 nm is less than 0.3 prior to the collection of fluorescence spectra. This finding indicates that inner-filter effects may have obscured changes in the redox signature of fluorescence spectra of the highly absorbing samples studied by Macalady and Walton-Day ( 2009 ).